Walking New York : Reflections of American Writers from Walt Whitman to Teju Cole - Miller, Stephen, 1941- (Book collections on Project MUSE., 2015)
"A literary walking tour of New York City as seen through the eyes of American and British writers. It's no wonder that New York has always been a magnet city for writers. Manhattan is one of the most walkable cities in the world. While many novelists, poets, and essayists have enjoyed long walks in New York, not all of them have had favorable impressions. Addressing an endlessly appealing subject, Walking New York is a study of twelve American writers and several British writers who walked the streets of New York and wrote about their impressions of the city in fiction, nonfiction, and poetry. Seen through the eyes of Walt Whitman, Herman Melville, William Dean Howells, Jacob Riis, Henry James, Stephen Crane, Theodore Dreiser, James Weldon Johnson, Alfred Kazin, Elizabeth Hardwick, Colson Whitehead, and Teju Cole, almost all the works in Walking New York are about Manhattan, with only Whitman and Kazin writing about Brooklyn. Though the writers were often irritated, disturbed, and occasionally shocked by what they saw on their walks, they were still fascinated by the city William Dean Howells called "splendidly and sordidly commercial" and Cynthia Ozick called "faithfully inconstant, magnetic, man-made, unnatural-the synthetic sublime." In this idiosyncratic guidebook to New York, celebrated writers ruminate on questions that are still hotly debated to this day: the pros and cons of capitalism and the impact of immigration. Many imply that New York is a bewildering text that is hard to make sense of. Returning to New York after an absence of two decades, Henry James loathed many things about "bristling" New York, while native New Yorker Walt Whitman both celebrated and criticized "Mannahatta" in his writings. Combining literary scholarship with urban studies, Walking New York reveals how this crowded, dirty, noisy, and sometimes ugly city gave these "restless analysts" plenty of fodder for their craft"--